2010
DOI: 10.1007/s10649-010-9257-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors that pre-service elementary teachers perceive as affecting their motivational profiles in mathematics

Christine M. Phelps

Abstract: The purpose of this study was to examine the sources that pre-service teachers (PSTs) use when they construct their self-efficacy beliefs and learning goals, which compose their motivational profiles. Pre-service elementary teachers (n=22) with different motivational profiles participated in narrative interviews designed to examine retrospectively their past experiences in mathematics and the effect of those experiences on their motivational profiles. Results reveal that participants relied on multiple sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 32 publications
0
11
0
2
Order By: Relevance
“…Even fewer are directed at PSTs, despite indications that teacher self-efficacy develops mainly during teacher education (Charalambous et al, 2008;Hoy & Spero, 2005). Mathematics teaching is an especially interesting context, since PSTs often express doubt about their self-efficacy in mathematics (Gresham, 2007), while the concepts of self-efficacy in mathematics and self-efficacy in teaching mathematics appear to be closely related (Briley, 2012;Phelps, 2010). Bandura (1977) described four sources of experience that may contribute to the formation of efficacy beliefs.…”
Section: Sources Of Self-efficacy At the Intersection Of Experience Amentioning
confidence: 99%
“…Even fewer are directed at PSTs, despite indications that teacher self-efficacy develops mainly during teacher education (Charalambous et al, 2008;Hoy & Spero, 2005). Mathematics teaching is an especially interesting context, since PSTs often express doubt about their self-efficacy in mathematics (Gresham, 2007), while the concepts of self-efficacy in mathematics and self-efficacy in teaching mathematics appear to be closely related (Briley, 2012;Phelps, 2010). Bandura (1977) described four sources of experience that may contribute to the formation of efficacy beliefs.…”
Section: Sources Of Self-efficacy At the Intersection Of Experience Amentioning
confidence: 99%
“…The benefits of the study for the research team were twofold, while the pre-service teachers develop as teachers through their action research, the teacher-educators had the opportunity to develop their teaching and approach to action research through what can be referred to as action research upon action research (Smith & Sela, 2005). The importance of reflection in teaching and teacher education is not new, and numerous authors have contributed their views on reflection, values, self-efficacy, and outcomes of reflective practice (Bloomfield, 2006;Bourke, Ryan, & Lidstone, 2012;Ditchburn, 2015;Phelps, 2010;Zeldin & Pajares, 2000). Kosnik and Beck (2000) in their research on action research found that it was difficult to assess the impact of doing action research in teacher education separately from the effects from other aspects of the professional experience.…”
Section: Discussion Of Case Studiesmentioning
confidence: 99%
“…Самоефикасност, један од основних концепата Бандурине (1997) теорије социокогнитивног учења, подразумева опажање сопствених капацитета и способности, когнитивних фактора, саморегулишућих процеса, као и очекивање успешности у одређеним ситуацијама. Уколико индивидуа верује у своју успешност и сопствено поседовање потенцијала за успешну реализацију активности, шансе за њен успех су веће, јер уверења особе о личној самоефикасности делују на саморегулацију мотивације (Ashford & LeCroy, 2010;Bagakas, 2011;Gutman, 2006;Linnenbrink & Pintrich, 2003;Meshak, 2013;Pajares & Schunk, 2001;Phelps, 2010;Schoenfeld, 1992).…”
Section: теоријске основе истраживањаunclassified